The Intersecting Ethnic Identity on LGB With Internalized Homophobia and Coming Out in Malaysia - Hieu, Sooh Peng; Ng, Jo Anne (2015)
In Malaysia, there has been less research that focus on gender, ethnic identity, internalized homophobia and coming out from closet within LGB communities. The study aim to find out whether level of ethnic identity and internalized homophobia related to coming out among LGB. Present study was carried by using snowball sampling method with the total number of 196 participants, 102 females, and 94 males. Revised Internalized Homophobia (IHP-R) scale, Outness Inventory (OI), and Revised Multigroup Ethnic Identity Measure (MEIM-R) were used for data collection. The result of study showed that there were significant gender difference in internalized homophobia, and significant negative correlation between internalized homophobia and coming out to Family and World. However, there were no significant correlation between level of ethnic identity and internalized homophobia, and no significant correlation between level of ethnic identity and coming out. The findings and results provided people to understand the minority stressors suffered by LGB.